Relasi Media Komunikasi Hibrid, Otoritas Adat, dan Solidaritas Religius Dalam Banjar Hindu di Kota Mataram - I Wayan Wijanaraga; Joko Prayitno (IAHN Gde Pudja Mataram, 2026)
This study aims to analyze the transformation of communication media within Banjar Gria Hita Pagutan Barat, Mataram City, and its implications for customary authority and religious solidarity in the Hindu community. Employing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of reduction, presentation, and conclusion verification. The findings reveal that banjar communication has evolved into a hybrid system that integrates digital media—particularly WhatsApp Groups—with traditional media such as paruman and bulletin boards. WhatsApp Groups serve to accelerate information dissemination, enhance coordination, and broaden community participation, while traditional media continue to function as sources of customary legitimacy and spaces for building social consensus. The integration of these media strengthens social cohesion, sustains the values of menyama braya and gotong royong, and supports the socio-religious life of the Hindu community. The study underscores that digitalization does not displace the role of customary institutions; rather, it reinforces them through adaptive communication practices. This research offers the concept of hybrid communication as a model for integrating technology, tradition, and spirituality within contemporary Hindu communities. Keywords: hybrid communication; Hindu banjar; customary authority; digital media; religious solidarity.